Customizable vs. Cookie-Cutter: Why Flexibility in Low-Code Platforms is Critical for Business Innovation - Okeke, Humphrey Emeka; Akinbolajo , Olayinka Demola (International Journal of Scientific Research and Modern Technology, 2023)
In the rapidly evolving landscape of business innovation, the choice between customizable and cookie-cutter low-code platforms has become a critical decision for organizations seeking to balance flexibility and efficiency. This article examines the limitations of cookie-cutter platforms, which rely heavily on predefined templates, and highlights the advantages of customizable platforms like RadSystems in addressing complex workflows and enabling tailored solutions. Through data analysis and real-world case studies, we demonstrate how customizable platforms foster rapid innovation, seamless integration of advanced technologies such as AI, and adaptability to changing regulations and customer demands. For instance, fintech startups leveraging RadSystems have successfully built adaptive applications that outpace competitors without costly redevelopment. The findings underscore the importance of flexibility in driving business innovation and meeting evolving market needs. By prioritizing customizable platforms, businesses can achieve greater scalability, operational efficiency, and competitive advantage.